Effect of adipose derived stem cells on ovariectomised Wistar rats - Oommen, Anitha; Al-Zahrani, Ibrahim Hassan (International Journal of Research in Medical Sciences, 2017)
Background: Various clinical trials are going to determine the efficacy of human Adipose Derived Stem Cells (hADSCs) in the treatment of degenerative diseases including osteoporosis. Stem cell therapy for osteoporosis is aimed at inducing new bone formation by the proliferation and differentiation of bone progenitor cells. The therapeutic potential of hADSCs has to be investigated in animal models of osteoporosis before suggesting it as a therapeutic option. Methods: hADSCs were cultured in the Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 4 mM L-glutamine and 110 mg/l sodium pyruvate, 10% Fetal Bovine Serum (FBS), 1% penicillin–streptomycin and non-essential amino acids. For osteogenic differentiation of hADSCs, cells were cultured as above then were exposed to osteogenic induction medium for seven days. Intravenous infusion of osteogenesis induced hADSCs was given to 20 ovariectomised Wistar rats three months after ovariectomy (test group) and 20 ovariectomised rats were kept as controls. Rats were sacrificed 35 days after infusion and tibial cross sections at the level of tibio-fibular joint were stained with H&E & Masson’s trichrome. The digital slide images were viewed using Aperio Image Scope software. Results: The results showed that there was new bone formation in the test group, indicated by osteoid formation and osteoblasts. There was significant increase in the cortical thickness in the test group when compared with the control group. There was no significant increase in trabecular volume when compared to the control group. Conclusions: hADSCs after osteogenic induction may have the potential to enhance new bone formation and may be useful in the treatment of osteoporosis.